Global mobility in ASEAN: promoting multi cultural diversity and inclusivity through AIMS - Yazrina Yahya,; Nordiana Mohd Nordin,; Abdul Latiff Ahmad,; Rosnani Boyak,; Harfiz Rasul Mohamad,; Nur Haiqal Rawlins Una Abdullah,; Ong, Chang Ee (Penerbit Universiti Kebangsaan Malaysia, 2020)
The trends in higher education have changed tremendously over the past decade. Knowledge is now an asset that moves between countries. The profound effort generates the globalization of universities, students and niche research. Hence international mobility program are gaining popularity as it gives significant outcomes for its students who had experienced mobility exchange. It is apparent that mobility had prepared the students to contribute to the global workforce, establish global networks and join the brain global circulation. Mobility exchange is seen to be the driving force for the students who are not able to study abroad to obtain an international degree. It is also seen to be giving opportunities to students to become “international” or global by studying abroad for a semester, which is more affordable for most students. Realizing the importance of mobility exchange, ASEAN have now taken the initiatives to encourage mobility among students. The students are going to exchange program either to ASEAN countries or elsewhere across the globe with the mission to become a global citizen with a global mindset. In promoting internationalization across ASEAN, SEAMEO-RIHED via its Asian International Mobility for Students (AIMS) program has laid out its pathway for students to go for mobility exchange. The paper will discuss the journey of AIMS and how its platform has promoted the multicultural diversity and inclusivity across ASEAN and support the One ASEAN Community establishment.